Multi-tissue expression and splicing data prioritise anatomical subsite- and sex-specific colorectal cancer susceptibility genes - Emma Hazelwood; Daffodil M. Canson; Benedita Deslandes; Xuemin Wang; Pik Fang Kho; Danny Legge; Andrei-Emil Constantinescu; Matthew A. Lee; D. Timothy Bishop; Andrew T. Chan; Stephen B. Gruber; Jochen Hampe; et al. (Nature Communications)
Abstract Genome-wide association studies have suggested numerous colorectal cancer (CRC) susceptibility genes, but their causality and therapeutic potential remain unclear. To prioritise causal associations between gene expression/splicing and CRC risk (52,775 cases; 45,940 controls), we perform a transcriptome-wide association study (TWAS) across six tissues with Mendelian randomisation and colocalisation, integrating sex- and anatomical subsite-specific analyses. Here we reveal 37 genes with robust causal links to CRC risk, ten of which have not previously been reported by TWAS. Most likely causal genes with evidence of cancer cell dependency show elevated expression linked to risk, suggesting therapeutic potential. Notably, SEMA4D, encoding a protein targeted by an investigational CRC therapy, emerges as a key risk gene. We also identify a female-specific association with CRC risk for CCM2 expression and subsite-specific associations, including LAMC1 with rectal cancer risk. These findings offer valuable insights into CRC molecular mechanisms and support promising therapeutic avenues.